2022
DOI: 10.1002/lt.26387
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus or Everolimus Improves Survival After Liver Transplantation for Hepatocellular Carcinoma: A Systematic Review and Meta‐Analysis

Abstract: The effects of mammalian target of rapamycin (mTOR) inhibitors (sirolimus [SRL] and everolimus [EVL]) on survival in liver transplantation (LT) recipients with hepatocellular carcinoma (HCC) remain the subject of intense research. Therefore, we performed this systematic review and meta-analysis to investigate the potential survival benefits of mTOR inhibitors (mTORis). Embase, PubMed, and Cochrane Central Register of Controlled Trials (CENTRAL) were searched for all randomized controlled trials (RCTs) and coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 36 publications
3
28
0
Order By: Relevance
“…[468][469][470] Recent meta-analysis reported better outcomes in mTORi group than non-mTORi groups in the 5-year RFS rate (ratio, 1.13; 95% CI, 1.02-1.26 in RCT and ratio, 1.17; 95 CI, 1.10-1.24 in cohort study). 471 Therefore, if there are no significant adverse events related to drugs, mTORi may be considered in LT recipients with HCC.…”
Section: Immunosuppression After Ltmentioning
confidence: 99%
See 1 more Smart Citation
“…[468][469][470] Recent meta-analysis reported better outcomes in mTORi group than non-mTORi groups in the 5-year RFS rate (ratio, 1.13; 95% CI, 1.02-1.26 in RCT and ratio, 1.17; 95 CI, 1.10-1.24 in cohort study). 471 Therefore, if there are no significant adverse events related to drugs, mTORi may be considered in LT recipients with HCC.…”
Section: Immunosuppression After Ltmentioning
confidence: 99%
“…Recent studies have shown that the use of mTORi may be helpful for reducing recurrence and prolonging survival in HCC patients after LT, but further studies are needed [ 468 - 470 ]. Recent meta-analysis reported better outcomes in mTORi group than non-mTORi groups in the 5-year RFS rate (ratio, 1.13; 95% CI, 1.02–1.26 in RCT and ratio, 1.17; 95 CI, 1.10–1.24 in cohort study) [ 471 ]. Therefore, if there are no significant adverse events related to drugs, mTORi may be considered in LT recipients with HCC.…”
Section: Liver Transplantationmentioning
confidence: 99%
“…The most important indication for LT is concurrent HCC and cirrhosis. For end-stage liver diseases, LT is the most effective strategy[ 7 ]. However, tumor recurrence remains a significant challenge.…”
Section: To the Editormentioning
confidence: 99%
“…A systematic review and meta-analysis reported that SRL or EVL improved one, two, three and five-year overall survival (OS) [randomised controlled trials: 1-year, relative risk (RR) =1.04, 95%CI: 1.00-1.08; 2-year, RR = 1.09, 95%CI: 1.02-1.16; 3-year, RR = 1.13, 95%CI: 1.04-1.24; 5-year, RR = 1.13, 95%CI: 1.02-1.26) vs (cohort studies: 1-year, RR = 1.13, 95%CI: 1.06-1.20; 2-year, RR = 1.24, 95%CI: 1.16-1.32; 3-year, RR = 1.24, 95%CI: 1.15-1.34; 5-year, RR = 1.17, 95%CI: 1.10-1.24)), respectively[ 7 ]. A 13% improvement in OS was demonstrated over five years, with 14% survival benefit in three years, and minimal risk of nephrotoxicity was noticed (RR = 0.75, 95%CI: 0.60-0.93) in the mTOR inhibitors group.…”
Section: To the Editormentioning
confidence: 99%
“…In this issue of Liver Transplantation , Yan et al ( 1 ) synthesize existing data through a systematic review and meta‐analysis to attempt to answer whether mammalian target of rapamycin (mTOR) immunosuppression protocols influence hepatocellular carcinoma (HCC) recurrence. This study updates prior meta‐analyses on the subject, which primarily included a limited number of observational studies.…”
mentioning
confidence: 99%